New candidate chromosomal regions for chordoma development - GÜNEY, AHMET İLTER; BAYRAKLI, FATİH (ELSEVIER SCIENCE INC, 2007)
Background: Chordomas are rare, slow growing, infiltrative tumors thought to arise from vestigial or ectopic notochord. Chordoma can occur along the axial skeleton, predominantly in the sphenooccipital, vertebral, and sacrococcygeal regions. Although most chordomas are sporadic, familial cases have also been reported. The most common molecular cytogenetic abnormalities in these tumors are monosomy of chromosome I and gain of chromosome 7. In addition, a variety of other chromosomal changes, which are associated with losses and gains of different chromosomes, have also been described in chordomas, such as 1q, 2p, 3p, 5q, 9p, 10, l2q, 13q, 17, and 20q. Methods: In this study, using molecular cytogenetics (iFISH), we have studied 1p36, 1q25, 3p13p14, 7q33, 17p13.1 (p53 gene locus), 2p13 (TGF-alpha locus), 6p12 (VEGF locus), and 4q26-q27 (bFGF/FGF2 locus) loci in chordoma tissues from seven patients with 7 primary tumors and 11 recurrences. Results: We found that chromosomes 1p36, 1q25, 2p13, and 7q33 are affected in primary chordomas, and these aberrations persist in recurrences. However, the chromosome 6p12 aberration was seen only in primary chordomas, but not in recurrences, indicating that this locus may be associated with chordoma genesis. Conclusions: Our descriptive data from interphase FISH analyses suggest that future studies should incorporate a larger number of patients and should focus on identifying the candidate genes in chordoma pathogenesis. Such studies may use a whole-genomic approach, in addition to the regions identified in this study and others. (C) 2007 Elsevier Inc. All rights reserved.
Keywords: chordoma; FISH; choromosomal abberations; SKULL-BASE CHORDOMAS; FAMILIAL CHORDOMA; CYTOGENETIC ANALYSIS; TUMOR; DNA; EXPRESSION; ABNORMALITIES; HYBRIDIZATION; EXPERIENCE; PROTEINS